1998
DOI: 10.1002/(sici)1521-4141(199806)28:06<1934::aid-immu1934>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Naturally activated CD4+ T cells are highly enriched for cytokine-producing cells

Abstract: Most T cells in a normal non-immunized individual are in a resting state. However, a small proportion of splenic T cells are large activated cells both in specific pathogen-free and antigen-free mice. To further elucidate the effector functions associated with these "naturally" activated CD4+ T cells, we have characterized the expression of various membrane markers, cytokine production and T helper activity by these cells. We show that naturally activated CD4+ T cells express activation markers and contain ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…Further observations, which are presented in Table 1, show that the 'helper activity', required to support thymocyte responses, can be abrogated by the removal of CD44 hi cells, but not by the removal of cells bearing high levels of CD45RB or CD62L. This surface phenotype of CD44 hi , CD45RB low and CD62L low is the same as 'naturally'-activated CD4 + T cells found in normal mice (36,37). Collectively, these observations lead us to suggest that the syngeneic (radiation resistant) CD4 + T h , which are required for the generation of allo-specific thymocyte responses and are present in spleen, are activated T cells.…”
Section: Resultsmentioning
confidence: 70%
“…Further observations, which are presented in Table 1, show that the 'helper activity', required to support thymocyte responses, can be abrogated by the removal of CD44 hi cells, but not by the removal of cells bearing high levels of CD45RB or CD62L. This surface phenotype of CD44 hi , CD45RB low and CD62L low is the same as 'naturally'-activated CD4 + T cells found in normal mice (36,37). Collectively, these observations lead us to suggest that the syngeneic (radiation resistant) CD4 + T h , which are required for the generation of allo-specific thymocyte responses and are present in spleen, are activated T cells.…”
Section: Resultsmentioning
confidence: 70%
“…Moreover, few IL-5-producing cells were detected in the culture of anti-CD3-stimulated CD4 ϩ CD25 ϩ T cells by intracellular cytokine analysis (data not shown). These observations suggest that the majority of CD4 ϩ CD25 ϩ T cells in nonimmunized DO10 mice differ from "naturally activated" CD4 ϩ T cells (24), because it has been shown that "naturally activated" CD4 ϩ T cells are large in size and rapidly produce a large amount of cytokines upon activation (24).…”
Section: Cd4 ϩ Cd25 ϩ T Cells In Nonimmunized Do10 Mice Differ From Nmentioning
confidence: 97%
“…Furthermore, the experiments also revealed that only ϳ6% of the cCD40L ϩ CD4 ϩ T cells were in the dividing phase (Table II). Previous studies have shown that the spleen contains a small number of naturally activated large T cells (30), which may contain preformed cCD40L. To study whether CD40L…”
Section: Cd4mentioning
confidence: 99%